Collaboration in crisis: Carer perspectives on police and mental health professional's responses to mental health crises. (24th June 2016) - Brennan, Alice; Warren, Narelle; Peterson, Violeta; Hollander, Yitzchak; Boscarato, Kara; Lee, Stuart
Abstract: For many situations involving a mental health crisis, carers (e.g. family or friends) are present and either attempt to help the person overcome the crisis or request assistance from professional services (e.g. mental health or police). Comparatively, little research has explored how carers experience the crisis, the professional response and how the nature of the response, in turn, impacts carers. The current study was conducted to explore these issues during individual interviews with nine carers who had previous contact with police and mental health services during a crisis response. Collected data described the definition and perceived impact of a mental health crisis for carers, how carers had experienced a crisis response from police and mental health services, and how the professional response had impacted on carers. Of importance was the finding that carers were often themselves traumatized by witnessing or being involved in the crisis, however, were rarely offered direct education or support to help them cope or prevent future crises. A number of carers described a reluctance to request assistance from professional services due to previous poor experiences. This highlighted the importance of implementing strategies to deliver more timely, respectful, specialist and collaborative crisis responses to improve carer and consumer outcomes.